2021
DOI: 10.1002/jrs.6214
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy in the quality analysis of dairy products: A literature review

Abstract: This work presents a review on the use of Raman spectroscopy in the evaluation of the quality control of dairy products. Milk and dairy products are globally extremely important foodstuffs both economically and nutritionally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Characterization, classification, and/or quality control of dairy products, fats/oils, and sugars have been investigated. 19,32,33 The acquired Raman spectra presented some strong peaks, medium and smaller peaks, and their attempted assignments are listed in Table II. Most Raman spectral regions selected fell within the fingerprint region near medium-intensity peaks, and/or near the high-intensity peak corresponding to –CH 2 /–CH 3 stretching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization, classification, and/or quality control of dairy products, fats/oils, and sugars have been investigated. 19,32,33 The acquired Raman spectra presented some strong peaks, medium and smaller peaks, and their attempted assignments are listed in Table II. Most Raman spectral regions selected fell within the fingerprint region near medium-intensity peaks, and/or near the high-intensity peak corresponding to –CH 2 /–CH 3 stretching.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy has been successfully applied in dairy products, such as milk, for quality and safety evaluation. 14,1719…”
Section: Introductionmentioning
confidence: 99%
“…The second review paper by Gouvêa Silva et al (Raman spectroscopy in the quality analysis of dairy products: A literature review, Universidade Federal de Juiz de Fora, Brazil) [40] deals with the evaluation of the quality control of dairy products such as milk. Dairy products are important foodstuffs which require the strict adherence to quality standards for production, industrialization, and commercialization.…”
Section: Biological Compoundsmentioning
confidence: 99%
“…In recent years, there has been a new phenomenon in food quality risks: some cheap products have been misrepresented as high-quality food. 6 However, according to the analysis of specific components in-line with national standards, further relevant research has found that their nutritional components and pollutant limits meet the requirements of food quality and safety regulations, and they are acceptable products. It is difficult for a single component index to allow an accurate judgment when detecting such quality problems.…”
Section: Introductionmentioning
confidence: 99%